Percepción de los Servicios que ofrece El iTUR del Gad Municipal de la Ciudad de Loja - Iñiguez Valencia, Karla Abigail (2024)
The research carried out on the perception of the services offered by the Tourist Information Office (iTUR) of the Municipal GAD of the City of Loja, is essential to improve the quality of service that is being provided to tourists who ask by specific information. Given the relevance of this topic, in this curricular integration work a general objective was proposed: Evaluate the perception of the service offered by the iTUR of the Municipal GAD of the City of Loja. Likewise, two specific objectives were determined: The first one to examine the perception of services and the second one to develop an improvement plan. To achieve the first objective, the form provided by MINTUR (Ministery of Tourism) was used to collect information on tourism companies, along with interviews with the director of the tourism department and workers to understand the quality of management in this institution. The SERVFPERF (Service Performance) method was applied, which, through its five dimensions, revealed the perception of tourists. The PESTEL (political, economic, social, technological, ecological and legal analysis) methodology was also used to identify the external factors that affect the tourist information Office. From these data, SWOT (strengths, weaknesses, opportunities and threats) analysis and Cross SWOT analysis was carried out, which led to the second objective, determining the necessary strategies to improve the service, which includes updating iTUR's social networks, training iTUR workers for a better customer service and the implementation of security equipment and information digitization programs.